CHARACTERIZATION AND DYNAMICS OF SURFACE FUEL OF CERRADO GRASSLAND IN JALAPÃO REGION – TOCANTINS, BRAZIL - Santos, Micael Moreira; Batista, Antonio Carlos; Silva, Allan Deyvid Pereira da; Ganassoli Neto, Eduardo; Barradas, Ana Carolina Sena; Giongo, Marcos (Floresta, 2020)
The aim of the present study was to evaluate the characteristics of surface fuel during the dry season in areas with different periods without the occurrence of burn, in the grasslands phytophysiognomy of the Cerrado in the Jalapão region of Brazil. Fuel sampling was conducted in areas with different periods without burning over four months during the dry season (May, June, August, and September). A total of 128 samples, named as data samples, were established, from which eight subsamples designated as parcels of fuel sampling were collected. In each parcel of fuel sample, we evaluated variables related to non-destructive methods such as the height of grass vegetation (Htg), litter height (Htl), number of species (Nsp), and number of individuals (Nin), as well as variables related to the destructive method for obtaining the fuel load. The fuel was separated according to its physiological state and diameter (time-lag). The Htg variable was highest and was stabilized by the second year post-burning. Nsp showed a reduced number of areas after four years without burning and in the last month of the dry season. The behavior of the dead grass fuel (Dg) load in the samplings collected in the first two months of the dry season was the only variable that increased in the different years without burning. These results are important for management initiatives of Cerrado grassland fuels in the Jalapão region.